PROBLEMS OF POVERTY REDUCTION BASED ON EFFICIENT USE OF LABOR RESOURCES IN THE INDUSTRY NETWORK - Doniyorova Shakhnoza Doniyorovna (Scholar Express Journals, 2023)
In the articlepoverty reduction factors are classified and systematized based on the effective use of labor resources in the industrial sector. It is scientifically proven that the activation of effective use of labor resources at the expense of internal resources that do not require large costs in the enterprises of the industrial network is one of the important factors for reducing poverty, which is considered an acute social problem at the country level.
Keywords: industrial sector; production; enterprise